Model Rasch sebagai Kerangka Acuan Penyusunan Alat Ukur - Asrijanty – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
This article is a review of the function of the Rasch model as a frame of reference in constructing instruments in social sciences, particularly for education and psychology. The argument of this article is that efforts to obtain an instrument which provides valid information can be done by utilizing the Rasch model in data analysis. The aims of this article are to examine: 1) the characteristics of the Rasch model as a measurement model; 2)the utilization of the Rasch model in test development. The examination of the Rasch model encompasses its characteristics and its paradigm in comparison with other measurement models, namely twoparameters logistic (2 PL model) model and three parameters logistic models (3 PL model;) and criticism of the Rasch model. The examinaton utilization of the Rasch model in test development includes its implication and application of the Rasch model in test development. This study shows that: 1) the characteristics and the paradigm of the Rasch model differ from the 2 PL model and 3 PL model ; 2)in line with its characteristics and its paradigm, the function of the Rasch model in test development is to guide and to diagnose problems in instrument. ABSTRAKArtikel ini merupakan kajian fungsi model Rasch sebagai kerangka acuan penyusunan alat ukur dalam ilmu sosial, khususnya dalan bidang pendidikan dan psikologi. Kajian ini didasari argumen bahwa usaha untuk memperoleh alat ukur yang memberi informasi yang valid dapat dilakukan dengan memanfaatkan model Rasch dalam analisis data. Tujuan kajian ini dimaksudkan untuk mengkaji: 1) karakteristik model Rasch sebagai model pengukuran; 2) penggunaan model Rasch dalam pengembangan tes. Kajian dilakukan dengan membahas karakteristik dan paradigma model Rasch disertai dengan perbandingan dengan model pengukuran lain, khususnya model logistik dua parameter (2PL) dan model logistik tiga parameter (3 PL), termasuk kritik yang sering diajukan terhadap model Rasch. Kajian penggunaan model Rasch dalam pengembangan tes dilakukan dengan membahas implikasi dan aplikasi model Rasch dalam analisis data untuk pengembangan instrumen. Hasil kajian menunjukkan bahwa: 1) model Rasch mempunyai karakteristik dan paradigma yang berbeda dari model 2 PL dan model 3 PL; 2) sesuai dengan karakteristik dan paradigma model Rasch, fungsi model Rasch dalam analisis data pengembangan instrumen, yaitu untuk memberi arah dan mendeteksi atau mendiagnosa adanya masalah pada instrumen.